KONSEP MISKIN MENURUT ISLAM DAN PEMERINTAH SERTA PENERAPANNYA PADA LEMBAGA ZAKAT - Alam, Putra; Putra, Trisno Wardy (Jurnal Ar-Ribh, 2020)
This research appears from the diversities of poverty standard which develop among people, each department has different standard to distribute the program in term of poor people. In mass media finds that when the social assistance to needy ones, there are increasing needy numbers, people admits that they are inculding the needy to gain the social assistance. So how Islam and government views? How zakat institutionsmake a clear definitions about concept of poor ?. The method uses qualitative, the characteristic of this research is to descript a case by understanding the meaning and factors, so that data analyzing wchich used is analytic descriptive. Data are collected by observation, interview and the last is summarizing. This research shows that the concept of poor in Islam is more complete then government version, if the government only see from the ability to fulfill basic needs. So Islam sees not only from basic needs but also spiritual sides such as thankfullnes, qona’ah, iffa an ect. The application of concept of poor in zakat institutions in this case BAZNAS has been succeed integrating between government and Islam.